2009
DOI: 10.1002/cmdc.200900019
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Trypanosoma brucei Active 1‐Alkyloxy and 1‐Benzyloxyadamantano 2‐Guanylhydrazones

Abstract: Treating African trypanosomiasis: The synthesis and biological evaluation of novel 1-alkyloxy and 1-benzyloxyadamantano 2-guanylhydrazones, their 1-dioxa congeners and two 1-benzyladamantano 2-guanylhydrazones is reported. Preliminary structure-activity relationship data were elucidated and lead compounds suitable for further optimization were discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Combining the guanylhydrazone pharmacophore, which is known to be a S-adenosylmethionine decarboxylase inhibitor and a trypanocidal motif by itself, with lipophilically substituted adamantane moieties, a synergistic effect of lipophilicity at C1 of the adamantane scaffold and the C2 functionality could be observed in compounds 195 , 359 199 , and 200 . 360 For this class of trypanocides, a decane- (or “oxadecane” substitution, for that matter) substituent at C1 was shown to be ideal in terms of in vitro trypanocidal potency. Lastly, oxaheterocyclic amines like oxaadamantane 198 361 and the secondary amine 201 362 have also been shown to display anti- T. brucei activity in vitro ; furthermore, the latter oxapolycyclic amine is devoid of any NMDA-receptor antagonism, which could be useful to avoid CNS-related side effects when using these compounds to combat T. brucei and other trypanosomes clinically.…”
Section: The First Hit: Adamantane Derivatives As Antivirals and Amentioning
confidence: 99%
“…Combining the guanylhydrazone pharmacophore, which is known to be a S-adenosylmethionine decarboxylase inhibitor and a trypanocidal motif by itself, with lipophilically substituted adamantane moieties, a synergistic effect of lipophilicity at C1 of the adamantane scaffold and the C2 functionality could be observed in compounds 195 , 359 199 , and 200 . 360 For this class of trypanocides, a decane- (or “oxadecane” substitution, for that matter) substituent at C1 was shown to be ideal in terms of in vitro trypanocidal potency. Lastly, oxaheterocyclic amines like oxaadamantane 198 361 and the secondary amine 201 362 have also been shown to display anti- T. brucei activity in vitro ; furthermore, the latter oxapolycyclic amine is devoid of any NMDA-receptor antagonism, which could be useful to avoid CNS-related side effects when using these compounds to combat T. brucei and other trypanosomes clinically.…”
Section: The First Hit: Adamantane Derivatives As Antivirals and Amentioning
confidence: 99%
“…Several studies have reported on the diverse aspects of the biological activity of guanylhydrazones [5][6][7][8]37]. While the antibacterial activity of the two guanylhydrazones 2,3-DMeB and 3,4-DMeB has previously been described [3], and focused in this study on their cytotoxicity, mutagenicity, and genotoxicity in different biological models.…”
Section: Discussionmentioning
confidence: 98%
“…antihypertensive, antibacterial, and antimalarial behavior, as well as the promotion of anti-pneumocystis and anti-trypanosomiasis [5][6][7][8]. A guanylhydrazone with especially interesting pharmacological activity is guanabenz (Wytensin ® ), an active central ␣2-adrenoceptor agonist used as antihypertensive agent [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, as potent trypanocidals. 6,7 Based on these findings and our involvement in the adamantane chemistry, [9][10][11][12][13][14][15][16][17][18][19][20] we report herein on the chemistry and biology of thiazole derivatives of the general type scaffold IV. The thiazole moiety is an important pharmacophore in many compounds used against several tropical infectious diseases.…”
Section: Introductionmentioning
confidence: 99%